The Impact of Mismatch Repair Status on Prognosis of Patients With Gastric Cancer: A Multicenter Analysis - Guan, Wen-Long; Ma, Yue; Cui, Yue-Hong; Liu, Tian-Shu; Zhang, Yan-Qiao; Zhou, Zhi-Wei; Xu, Jian-Ying; Yang, Li-Qiong; Li, Jia-Yu; Sun, Yu-Ting; Xu, Rui-Hua; Wang, Feng-Hua; et al. (Frontiers in Oncology, 2021)
Background: The clinical role of DNA mismatch repair deficiency (dMMR)/ microsatellite instablilty-high (MSI-H) in gastric cancer is still controversial. We aimed to analyze the relationship between dMMR/MSI-H and clinicopathological features along with survival. Methods: Patients who were diagnosed as gastric cancer at 3 big cancer centers in China from 2015 to 2020 were evaluated retrospectively. MMR/MSI status was assessed using immunohistochemistry/polymerase chain reaction (PCR). Clinical and pathological data was collected from medical record system. Results: 196 patients with dMMR/MSI-H status were enrolled for analysis. The prevalence of MSI-H/dMMR in gastric cancer was 6.6%. Another 694 pMMR GC patients were enrolled for comparison. Compared to pMMR patients, dMMR/MSI-H patients were associated with older age, female predominance, distal location in stomach, earlier TNM stage, intestinal subtype, better differentiation, and more with negative HER2 status. The median overall survival (OS) of dMMR/MSI-H group was better than the pMMR/MSS group (not reached vs 53.9 months, P=0.014). Adjuvant chemotherapy had no impact in both disease-free survival (DFS) and OS of dMMR/MSI-H patients (P=0.135 and 0.818, respectively). dMMR/MSI-H patients had poorer response and progression-free survival (PFS) of first-line chemotherapy, though it was not statistically significant (p=0.361 and 0.124, respectively). Conclusions: dMMR/MSI-H GC patients have specific clinico-pathological characteristics and with better prognosis than pMMR patients.